COMMUNICATION AS A SIGNIFICANT FACTOR OF EXISTING AND DEVELOPING OF MAN AND SOCIETY - Сластенко, Е. Ф. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the role and place of human communication in social life.